'To another's house':i the experiences of Muslim young people in foster care. (October 2018) - Pitcher, David; Jaffar, Shabana
Cultural confusion is a common experience among children in foster care. But it can be especially severe for Muslims when their faith, traditional values and way of life are disrespected and when this is exacerbated by removal from familiar home environments. This article describes the experiences of young people affected by this and critically examines how their situation matches the definitions of good practice in agencies and professionals seeking to help them. Four issues emerged: the child's confusion surrounding separation and moving to somewhere strange; identifying the right placement; intervening in a way that offers children future choices; and the ever-present risk of discrimination. In each of these situations, well-meaning and firmly established fostering practices can be insensitive to the needs and wishes of Muslim children. This confounds their understanding of their self, depresses their sense of social belonging and demands they adjust in order to survive. The article makes recommendations to support Muslim adolescents entering care and to improve the practice of the professionals and agencies responsible for them. The dearth of specialist therapeutic services is highlighted, along with suggestions for future research.